2020
DOI: 10.5194/acp-2020-142
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons (PAHs), oxy- and nitro-PAHs in ambient air of Arctic town Longyearbyen, Svalbard

Abstract: Abstract. Polycyclic aromatic hydrocarbons (PAHs) are not declining in Arctic air despite reductions in their global emissions. In Svalbard, the Longyearbyen coal-fired power plant is considered to be one of the major local source of PAHs. Power plant stack emissions and ambient air samples, collected simultaneously 1 km (UNIS) and 6 km (Adventdalen) transect distance, were analyzed (gaseous and particulate phases separately) for 22 nitro-PAHs, 9 oxy-PAHs and 16 parent PAHs by GC/ECNI/MS and GC-MS/MS. Results … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Moreover, Niu et al (2017) showed extremely high mean values of BaP in PM2.5 within Beijing-Tianjin-Hebei region (6.87-18.30 ng m -3 , Table 3). The mean BaP levels in other large urban/industrial regions of Asia, such as in Seoul (2.55 ng m -3 , Lee et al 2006), were much higher compared to Longyearbyen in Norway (0.89 ng m -3 , Drotikova et al 2020). It was also found that BaP concentrations in TPM at urban traffic/residential sites in Europe (Pietrogrande et al, 2011, Martellini et al, 2012, Siudek, 2018, Šišovic et al 2013, North America (Liu et al, 2017) and Australia (Mishra et al, 2016) were much lower than in similar urban areas of India (Ray et al, 2017) and China (Shi et al2015, Ma et al, 2018.…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…Moreover, Niu et al (2017) showed extremely high mean values of BaP in PM2.5 within Beijing-Tianjin-Hebei region (6.87-18.30 ng m -3 , Table 3). The mean BaP levels in other large urban/industrial regions of Asia, such as in Seoul (2.55 ng m -3 , Lee et al 2006), were much higher compared to Longyearbyen in Norway (0.89 ng m -3 , Drotikova et al 2020). It was also found that BaP concentrations in TPM at urban traffic/residential sites in Europe (Pietrogrande et al, 2011, Martellini et al, 2012, Siudek, 2018, Šišovic et al 2013, North America (Liu et al, 2017) and Australia (Mishra et al, 2016) were much lower than in similar urban areas of India (Ray et al, 2017) and China (Shi et al2015, Ma et al, 2018.…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…OCS has also been detected in air samples from the Alps (Kirchner et al, 2016), and 1,2,3,4-tetrachlorobenzene has been measured in sediments in Arctic Alaska (Gubala et al, 1995) but to our knowledge not in Arctic air before; 1,9-benz-10-anthrone, 9-fluorenone, 9,10-anthraquinone and 4H-cyclopenta[def]phenanthren-4-one have been reported in aerosols as total suspended particles from the Alert station, Canada (Singh et al, 2017). Besides that, they were detected, among further oxy-and nitro-PAHs, in the emissions from a local point source in Longyearbyen, Svalbard (coal-fired power plant) (Drotikova et al, 2020). Most of the known Arctic contaminants were classified as L1 as a result of available standards.…”
Section: Organic Compounds Previously Detected In Arctic Mediamentioning
confidence: 98%
“…PAHs in SPM samples were Soxhlet extracted with a solvent solution (the mixture of n-hexane and dichloromethane, 500 ml/L of each) for 24 h according to Chiu et al ( 2013a ). The extracts were then concentrated to about 3 ml on a rotary evaporator for the clean-up procedure (Drotikova et al 2020 ). The collected eluent from the clean-up procedure was concentrated to 1 ml on a rotary evaporator and stored at 4 °C till analysis (Hassan 2006 ).…”
Section: Methodsmentioning
confidence: 99%